Clinicopathologic evaluation of cytopenic patients with isolated trisomy 8: a detailed comparison between idiopathic cytopenia of unknown significance and low-grade myelodysplastic syndrome. Issue 3 (4th March 2017) - Petrova-Drus, Kseniya; Hasserjian, Robert; Pozdnyakova, Olga; Dal Cin, Paola; Mathew, Susan; Margolskee, Elizabeth; Orazi, Attilio; Geyer, Julia T.
Abstract: The significance of an isolated trisomy 8 (+8) in the diagnosis of myelodysplastic syndrome (MDS) is not well established. It is common in MDS, but is not considered as an MDS-defining abnormality in the absence of morphologic dysplasia. We evaluated two groups of patients with isolated +8 and either low-grade MDS (LG-MDS) or idiopathic cytopenia of undetermined significance (ICUS). At presentation, ICUS patients had a lower platelet count (85.0 vs 163.5 × 10 9 cells/L; p  = 0.02), while MDS patients had more frequent incidence of isolated anemia (64% vs 0%, p  = 0.007). A subset (36%) of ICUS patients progressed to MDS or AML. These patients presented with more severe neutropenia (0.9 vs 3.1 × 10 3 /μL, p  = 0.01) and a trend toward a higher proportion (>50%) of +8 metaphases compared to those that did not progress ( p  = 0.05). Thus, ICUS patients with isolated +8 may progress to MDS and AML and deserve close clinical follow-up.